Surgical Management of the Thick-Skinned Nose - Davis, Richard E.; Hrisomalos, Emily N. (Facial Plastic Surgery, 2018)
When executed properly, open structure rhinoplasty can dramatically improve the consistency, durability, and quality of the cosmetic surgical outcome. Moreover, in expert hands, dramatic transformations in skeletal architecture can be accomplished with minimal risk and unparalleled control, all while preserving nasal airway function. While skeletal enhancements have become increasingly more controlled and precise, the outer skin-soft tissue envelope (SSTE) often presents a formidable obstacle to a satisfactory cosmetic result. In noses with unusually thick skin, excessive skin volume and characteristically hostile healing responses frequently combine to obscure or sometimes even negate cosmetic skeletal modifications and taint the surgical outcome. For this challenging patient subgroup, care must be taken to optimize the SSTE using a graduated treatment strategy directed at minimizing skin thickness and controlling unfavorable healing responses. When appropriate efforts are implemented to manage thick nasal skin, cosmetic outcomes are often substantially improved, sometimes even negating the ill-effects of thick skin altogether.
Keywords: thick nasal skin; nasal SMAS debulking; nasal skin stretching; skin closing tension; subdermal plexus